PENGEMBANGAN BAHAN AJAR MATEMATIKA BERBASIS ETNOMATEMATIKA KRATON YOGYAKARTA - Annis Deshinta Ayuningtyas; Dafid Slamet Setiana (UNIVERSITAS MUHAMMADIYAH METRO, 2019)
Culture-based learning allows teachers and students to actively participate based on the culture they already know so that optimal learning outcomes can be obtained. One that can bridge between culture and education, especially mathematics is ethnomathematics. For this reason, it is necessary to plan teaching materials that are by the characteristics of mathematics learning based on the Yogyakarta Palace of Ethnomathematics. This study aims to develop a valid, practical, and effective ethnomathematics-based mathematics teaching material in Yogyakarta Palace. This research develops mathematics teaching materials based on the Ethnomathematics of Yogyakarta Palace. The product was developed using a 4-D development model developed by Thiagarajan, which consisted of the define, planning, develop and disseminate stages. The products produced are the ethnomathematics-based mathematics teaching materials in Yogyakarta in the form of Mathematics Modules and Student Activity Sheets. After going through the validation stage by experts, the products developed are included in the valid category. From the results of product trials, it is known that the products produced are included in practical and effective criteria